Self-Care in Type 2 Diabetes Patients with Urgency Lower Limb Amputation: The Influence of Sex, Marital Status and Previous Amputations - Domingos, Simone Aparecida; Franca, Carolina Nunes; Tuleta, Izabela; Costa Rezende Barbosa, Marianne Penachini da [UNESP]; Lacerda Bachi, Andre Luis; Neves, Lucas Melo (Dove Medical Press Ltd, 2021)
Aim: Lower limb amputation (LLA) is a severe consequence of type 2 diabetes mellitus (T2DM), and can affect up to 1% of T2DM patients, leading to an increased risk of premature mortality. Among the factors to predict LLA, it has been highlighted sex, marital status, and previous amputation. However, there is a lack of information about the association between these predictive factors, self-care, and urgency LLA in T2DM patients. Purpose: To verify the behavior of self-care and to relate it with the predictive factors (sex, marital status, and previous amputation) in urgency LLA T2DM patients. Patients and Methods: Non-interventional study, with 106 T2DM patients who were in the postoperative period of urgency LLA caused by complications resulting from T2DM. A structured questionnaire was used for sociodemographic and clinical characterization of the sample as well as the Summary of Diabetes Self-Care Activities (SDSCA) tool. It was used the Wilcoxon, Friedman, and Mann-Whitney tests (median, nonparametric populations) to assess the significance of the differences between groups (sex, marital status, and previous amputation), also Spearman correlation coefficient to assess the association between the data (comparison between diagnostic time, sex, previous amputation, ethnicity and systolic arterial hypertension) and a logistic regression analysis considering the item SDSCA related to sex, age and marital status (with partner). Results: Significant differences (p<0.05) in the questions Specific Food and Foot care were found when the participants were grouped by sex. In the relation to marital status, significant differences (p<0.05) were observed for the question Specific Food. No differences were found between groups with or without previous amputation. Conclusion: By SDSCA tool, we were able to report that T2DM patients submitted to urgency LLA presented differences in self-care, particularly for sex and marital status.
Keywords: self-care activities; surgery; diabetes mellitus; food; foot care